Enumeration of Dumont permutations avoiding certain four-letter patterns - Alexander Burstein; Opel Jones (Discrete Mathematics & Theoretical Computer Science, 2021)
In this paper, we enumerate Dumont permutations of the fourth kind avoiding or containing certain permutations of length 4. We also conjecture a Wilf-equivalence of two 4-letter patterns on Dumont permutations of the first kind.